Multifactorial dysphagia: Azygos vein aneurysm (AVA) and esophagogastric junction outflow obstruction (EGJOO). (June 2021) - Morton, Scott; Grubic, Andrew D.; Ayazi, Shahin; Muluk, Satish C.; Fernando, Hiran C.; Jobe, Blair A.
Abstract: Introduction: Vascular impingement of the esophagus is a rare cause of dysphagia, and is most commonly due to aortic arch anomalies such as arterial lusoria. Dysphagia resultant from venous compression is even further less likely. Presentation of case: We present a highly unusual case of dysphagia secondary to a large aneurysm of the azygous vein near its confluence with the superior vena cava, which was managed with endovascular modalities. Despite initial treatment success, patient reported some intermittent solid food dysphagia, and was also found to have esophagogastric junction outflow obstruction (EGJOO) on high resolution impedance manometry (HRIM) which was successfully managed with surgical myotomy and partial fundoplication. Discussion: The azygos vein has an intimate anatomic relationship with the esophagus as it traverses the posterior mediastinum. Because of this anatomic association, the azygos vein may present a point of esophageal obstruction in the setting of significant pathology. Conclusion: This case highlights the possibility of multifactorial causes of dysphagia, and that HRIM is a key aspect of this workup. Additionally we discuss the pertinent anatomy, diagnosis, and treatments for azygos vein aneurysm and EGJOO. Highlights: Vascular impingement of the esophagus is a rare cause of dysphagia. This type of dysphagia is most commonly due to aortic arch anomalies such as arterial lusoria. The azygos vein may present a point of esophageal obstruction in the setting of significant pathology. Endovascular therapy in selected patients can provide resolution of dysphagia in patients with azygos vein aneurysm. There is possibility of multifactorial causes of dysphagia, and high resolution manometry is a key aspect of this workup.